Tablet PCs for Dummies - Stevenson, Nancy (Hungry Minds, 2011)
Geared toward the general user of the Tablet PC, this text includes case studies of how the Tablet PC can be used in vertical applications such as healthcare and for enhanced productivity throughout an organization.